2000
DOI: 10.1144/gsl.sp.2000.173.01.06
|View full text |Cite
|
Sign up to set email alerts
|

A Geotraverse Across Northwestern Turkey: Tectonic Units of the Central Sakarya Region and their Tectonic Evolution

Abstract: In the Central

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
100
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 22 publications
2
100
1
3
Order By: Relevance
“…In this mélange north of Eskişehir, Göncüoğlu et al (2000) reported late Bathonian-early Tithonian and latest Hauterivian-early Aptian radiolarian cherts (determined by U. K. Tekin) associated to MORB-like pillow basalts (Figure 3,no. 6).…”
Section: Dağküplü Mélangementioning
confidence: 89%
See 4 more Smart Citations
“…In this mélange north of Eskişehir, Göncüoğlu et al (2000) reported late Bathonian-early Tithonian and latest Hauterivian-early Aptian radiolarian cherts (determined by U. K. Tekin) associated to MORB-like pillow basalts (Figure 3,no. 6).…”
Section: Dağküplü Mélangementioning
confidence: 89%
“…However, none of these fossils are illustrated, and the relationship between each other, their stratigraphic position and their age assignment remains doubtful. Tekin and Göncüoğlu (2007) and Tekin and Göncüoğlu (2008); (4) Tekin and Göncüoğlu (2009); (5) ; (6) Göncüoğlu et al (2000); (7) Göncüoğlu et al (2006b); (8) Yalınız et al (in prep. ) in Göncüoğlu et al (2006b); (9) Göncüoğlu et al (2006a), Göncüoğlu et al (2010) and Tekin et al (2002); (10) Servais (1982); (11) Bragin and Tekin (1996); (12) Rojay et al (2004); (13) Çelik (2010) and Üner (2010) in Tekin, Çelik et al (2012); (14) Tüysüz and Tekin (2007); (15) Boccaletti et al (1966); (16) Bozkurt et al (1997).…”
Section: Age and Type Of Blocksmentioning
confidence: 99%
See 3 more Smart Citations